Brachycephalic airway syndrome: management of post‐operative respiratory complications in 248 dogs. Issue 5 (9th February 2020) - Lindsay, B; Cook, D; Wetzel, J‐M; Siess, S; Moses, P
Abstract : Objective: As ownership of brachycephalic dog breeds rises, the surgical correction of components of brachycephalic airway syndrome (BAS) is increasingly recommended by veterinarians. This study's objective was to describe the incidence of, and strategies for the management of post‐operative respiratory complications in brachycephalic dogs undergoing surgical correction of one or more components of BAS. Methods: Medical records of 248 brachycephalic dogs treated surgically for BAS were retrospectively reviewed for demographic information, procedures performed, post‐operative complications and treatment implemented, hospitalisation time, and necessity for further surgery. Results: Pugs, Cavalier King Charles Spaniels and British Bulldogs were the most commonly encountered breeds. Dogs which experienced a complication were significantly older (mean was 5.5 years, compared with 4.1 years [P < 0.01]). Fifty‐eight dogs (23.4%) had complications which included: dyspnoea managed with supplemental oxygen alone (7.3%, n = 18), dyspnoea requiring anaesthesia and re‐intubation (8.9%, n = 22), dyspnoea necessitating treatment with a temporary tracheostomy (8.9%, n = 22), aspiration pneumonia (4%, n = 10), and respiratory or cardiac arrest (2.4%, n = 6). Five of the 22 dogs requiring anaesthesia and re‐intubation deteriorated 12 or more hours after post‐surgical anaesthetic recovery. The overall mortality rate in this study was 2.4% (n = 6). Age, concurrent airway pathology, and emergency presentation significantly predicted post‐operative complications. Conclusion: Our data show the importance of close monitoring for a minimum of 24 h following surgery by an experienced veterinarian or veterinary technician. Surgical intervention for BAS symptomatic dogs should be considered at an earlier age as an elective procedure, to reduce the risk of post‐operative complications.